The Correlation of L-citrulline Levels with Blood Pressure in Severe Preeclampsia - Hudila Rifa Karmia; Afriwardi Afriwardi; Hirowati Ali; Johanes Cornelius Mose; Yusrawati Yusrawati (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Based on 'vascular disorder of pregnancy' terminology, preeclampsia primarily was not a hypertensive disorder, but a vascular disorder (general vasospasm) in pregnancy due to idiopathic etiology. The overall incidence of preeclampsia was 5-14% of all pregnancies. One of the substances responsible for regulating vascular tone is nitric oxide (NO), which produced in endothelial blood vessels. NO and L-citrulline are produced altogether by the reaction between L-arginine and oxygen. L-citrulline levels reflected NO production. This study was aimed to assess the correlation between the L-citrulline level and blood pressure in severe preeclampsia.METHODS: This cross-sectional study was done in Dr. M. Djamil Central General Hospital, Padang, Indonesia The sample size was 36 samples of pregnant women with severe preeclampsia and had yet been given antihypertensive therapy. Sampling was done by consecutive sampling from Obstetrics and Gynecology Division. After maternal examination and measurements L-citrulline levels of cubital venous blood by using enzyme-linked immunosorbent assay (ELISA) method, Pearson correlation was performed to assess the relationship between variables for normally distributed data and Spearman's correlation for abnormal distribution data with significance level p<0.05.RESULTS: Means of L-citrulline levels, systolic blood pressure, diastolic blood pressure, and arterial pressure (MAP) were 87.21 nmol/mL, 179.4 mmHg, 108.3mmHg, and 132.1 mmHg, respectively. Correlation of the L-citrulline level with systolic blood pressure, diastolic blood pressure, and MAP were -0.08, -0.175, and -0.136 (p>0.05), respectively.CONCLUSION: L-citrulline levels had no correlation with blood pressure in severe preeclampsia.KEYWORDS: L-citrulline levels, blood pressure, severe preeclampsia